Handbook of terrorism in the Asia-Pacific - Gunaratna, Rohan; Kam, Stefanie (Imperial College Press insurgency and terrorism series, 2016)
This is a concise and readable handbook which examines the origins of the current wave of terrorism across countries in Southeast Asia, South Asia, Northeast Asia and the Pacific, and identifies emerging trends and new forms of terror that have altered the landscape and rendered the region increasingly vulnerable to asymmetric attacks.